Nutrition promotion messages: The effect of information on consumer sensory expectations, experiences and emotions of vitamin A-biofortified sweet potato - Lagerkvist, Carl Johan; Okello, J.J.; Muoki, Penina Ngusye; Heck, S.; Prain, Gordon (Elsevier, 2016)
Vitamin A deficiency (VAD) is a major public health problem in many developing countries globally. It is estimated that 250 million children under the age of five years suffer from clinical VAD. The effects of VAD include eye damage, weakened immunity and general increases in the incidence and severity of infectious diseases and mortality associated with e.g. birth-related complications, measles and diarrhoea among children. Biofortification is an essential strategy to alleviate VAD by incorporation of micronutrients into food staples through conventional breeding processes. However, vitamin A biofortification involves changes in other product attributes such as colour and taste that may be undesirable to some consumers. This study investigated how information about vitamin A biofortification influences the expected and actual sensory evaluation and the emotions evoked through actual tasting. For this, 501 randomly selected caregivers of children aged less than five years or pregnant women in western Kenya participated in a field information experiment combined with sensory testing of vitamin A-biofortified orange-fleshed sweet potato (OFSP). Surprisingly, the results showed that detailed information about nutritional benefits decreased consumer acceptance. Information about attribute drawbacks had discriminatory effects only in relation to expected taste and experienced texture. The findings indicated that the appropriateness of the nutritional aspect of OFSP was related to the information treatment and to household food insecurity status, but not to income or age of participants. An EmoSemio profile indicated a positive effect of nutrition information on emotions that did not correspond to the sensory assessment. These results raise important questions relating to how nutrition information should be provided to generate consumer acceptance and adoption of OFSP.